Clean Heat Standards: Foundations, Policy Mechanisms, and Recent Developments - Jan Rosenow; Marion Santini; Richard Cowart; Sam Thomas; Duncan Gibb; Richard Lowes (Energies)
Clean heat standards (CHS) represent a promising policy mechanism to drive the decarbonization of space and hot water heating, a significant contributor to global greenhouse gas emissions. This paper provides an introduction to CHS, which set targets for heat decarbonization for heating market actors. We explore their design features, implementation approaches, and potential synergies with other policy instruments. The analysis focuses on their role in complementing fossil fuel phaseout policies, accelerating market transformation, and addressing key barriers. Drawing on examples from existing and proposed policies worldwide, the paper examines the potential impacts of clean heat standards placed on heating appliance manufacturers, energy companies, and end users. It also considers the importance of integrating these standards into broader energy and environmental policy frameworks to achieve equitable and efficient outcomes. The findings suggest that while clean heat standards have substantial potential to reduce emissions and advance energy transition goals, their effectiveness will depend on careful design, robust enforcement, and alignment with complementary policies. This paper aims to provide policymakers, researchers, and stakeholders with a foundational understanding of clean heat standards and their role in fostering sustainable heating solutions.